(untitled) (Szociológiai Szemle, 2023)
While appreciating the novelty of Ákos Huszár’s model, the article criticizes his normative concept of capitalism by drawing the attention to the essential differences between postsocialist capitalism and the normatively understood West-European and Anglo-Saxon capitalist development. Privatization has never been accepted by Hungarian society as legitimate. The dispossession of the working people, who were the “owners” of property in principle, reinforced unequal competition. This undermined social trust in the established norms and the new democracy, which rendered democratic institutions essentially fragile in Hungary.